2018
DOI: 10.1080/19396368.2018.1481465
|View full text |Cite
|
Sign up to set email alerts
|

Per- and polyfluoroalkyl substances impact human spermatogenesis in a stem-cell-derived model

Abstract: CDC: Centers for Disease Control; DMSO: dimethyl sulfoxide; GHR: growth hormone receptor; hESCs: human embryonic stem cells; PFASs: per- and polyfluoroalkyl substances; PFCs: perfluorinated compounds; PFNA: perfluorononanoic acid; PFOS: perfluorooctanesulfonic acid; PFOA: perfluorooctanoic acid; PLZF: promyelocytic leukemia zinc finger; ROS: reactive oxygen species; HILI: RNA-mediated gene silencing 2; SSC: spermatogonial stem cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 63 publications
(119 reference statements)
0
18
0
3
Order By: Relevance
“…hESCs were pasaged using ReLeSR (STEMCELL Technologies) and plated onto Matrigel (Corning Life Sciences) coated plates as described 32,34 . Differentiation into spermatogenic lineages were conducted as previously described [32][33][34][35] with mouse STO cells for feeder cells or directly onto Matrigel. Medium was gassed every other day with a blood gas mixture (5% carbon dioxide, 5% oxygen, and 90% nitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…hESCs were pasaged using ReLeSR (STEMCELL Technologies) and plated onto Matrigel (Corning Life Sciences) coated plates as described 32,34 . Differentiation into spermatogenic lineages were conducted as previously described [32][33][34][35] with mouse STO cells for feeder cells or directly onto Matrigel. Medium was gassed every other day with a blood gas mixture (5% carbon dioxide, 5% oxygen, and 90% nitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…We were then able to simulate male exposure by differentiating WA01 human embryonic stem cells in the presence of 2,2′,4,4′,5,5′-hexabromobiphenyl (PBB153), into spermatogonial stem cells, primary and secondary spermatocytes and, finally, into spermatids. We previously demonstrated that this model mimics major components of human spermatogenesis 32 and have utilized this model to examine impacts of other environmental exposures [33][34][35] . Additionally, our in vitro spermatogenesis model has been independently replicated, highlighting its reproducibility 36 .…”
Section: Pbb153 Decreases Methylation At Icrs Of Imprinting Genes In mentioning
confidence: 99%
“…Molecular mechanisms of PFASs reproductivity are poorly known, and the number of publications reporting their effect on the human reproductive system is limited. Analyses with the use of the innovative in vitro model of spermatogenesis carried out on stem cells indicated that PFASs (PFOS, PFOA and PFNA), independently and as a mixture, caused no changes of transmembrane mitochondrial potential, did not intensify reactive oxygen species (ROS) generation and did not decrease viability of spermatogonia, spermatocytes (primary and secondary) or spermatidia [ 209 ]. However, this study demonstrated that selected PFASs could have a long-term effect on fertility by exhaustion of spermatogonia pool and by disturbance of function of primary spermatocytes caused by reduction of expression of markers specific for these cells.…”
Section: Endocrine Disruption Caused By Pfassmentioning
confidence: 99%
“…Epidemiological studies have linked PFAS exposure to increased cholesterol levels[47]. SSCs exposed to PFAS did not experience a decrease in germ cell viability, an increase in reactive oxygen species (ROS), or reduced cell viability[48].…”
Section: Heavy Metalsmentioning
confidence: 99%